UPAYA DEWAN KELUARGA MASJID DALAM MENINGKATKAN PEMAHAMAN DAN PENGETAHUAN TENTANG FUNGSI MASJID BAGI WARGA MASYARAKAT - Aam Amanah (Universitas Insan Cendekia Mandiri, 2019)
The problem in this research is the notion just a place to pray and study, but as a center of muamalah, education and many others. Descriptive method qualitative data collection techniques interview, observadi and documentation and questionnaires. Subjects were mosque caretakers, mothers and teenagers study mosques. The research objective is to obtain data about the management efforts to improve knowledge DKM mothers and teens about the function of the mosque and inhibiting factors in fostering and supporting mothers and adolescents through taklim. Results of research conducted so beragan and varied, participants are dominated by mothers and teenagers. Conclusion DKM efforts in improving the understanding and knowledge neighbor function of the mosque has a very important role, as a driving force of society, as an agent of change.